True Mass and Atmospheric Composition of the Nontransiting Hot Jupiter HD 143105 b - Luke Finnerty; Yinzi Xin; Jerry W. Xuan; Julie Inglis; Michael P. Fitzgerald; Shubh Agrawal; Ashley Baker; Randall Bartos; Geoffrey A. Blake; Benjamin Calvin; Sylvain Cetre; Jacques-Robert Delorme; et al. (The Astronomical Journal)
We present Keck/KPIC Phase II K -band observations of the nontransiting hot Jupiter HD 143105 b. Using a cross-correlation approach, we make the first detection of the planetary atmosphere at ${K}_{{\rm{p}}}=18{5}_{-13}^{+11}$ km s ^−1 and an inferior conjunction time 2.5 hr before the previously published ephemeris. The retrieved K _p value, in combination with the orbital period, mass of the host star, and lack of transit detection, give an orbital inclination of $7{8}_{-12}^{° +2}$ and a true planet mass of 1.23 ± 0.10 M _J . While the equilibrium temperature of HD 143105 b is in the transition regime between noninverted and inverted atmospheres, our analysis strongly prefers a noninverted atmosphere. Retrieval analysis indicates the atmosphere of HD 143105 b is cloud free to approximately 1 bar and dominated by H _2 O absorption ( ${logH}_{2}{{\rm{O}}}_{MMR}=-3.{9}_{-0.5}^{+0.8}$ ), placing only an upper limit on the CO abundance ( ${logCO}_{MMR}\lt -3.7$ at 95% confidence). We place no constraints on the abundances of Fe, Mg, or ^13 CO. From these abundances, we place an upper limit on the carbon-to-oxygen ratio for HD 143105 b, C/O < 0.2 at 95% confidence, and find the atmospheric metallicity is approximately 0.1 × solar. The low metallicity may be responsible for the lack of a thermal inversion, which at the temperature of HD 143105 b would likely require significant opacity from TiO and/or VO. With these results, HD 143105 b joins the small number of nontransiting hot Jupiters with detected atmospheres.